The subseafloor crustal biosphere: Ocean’s hidden biogeochemical reactor - Robador, Alberto (Frontiers in Microbiology, 2024)
Underlying the thick sediment layer in ocean basins, the flow of seawater through the cracked and porous upper igneous crust supports a previously hidden and largely unexplored active subsurface microbial biome. Subseafloor crustal systems offer an enlarged surface area for microbial habitats and prolonged cell residence times, promoting the evolution of novel microbial lineages in the presence of steep physical and thermochemical gradients. The substantial metabolic potential and dispersal capabilities of microbial communities within these systems underscore their crucial role in biogeochemical cycling. However, the intricate interplay between fluid chemistry, temperature variations, and microbial activity remains poorly understood. These complexities introduce significant challenges in unraveling the factors that regulate microbial distribution and function within these dynamic ecosystems. Using synthesized data from previous studies, this work describes how the ocean crustal biosphere functions as a continuous-flow biogechemical reactor. It simultaneously promotes the breakdown of surface-derived organic carbon and the creation of new, chemosynthetic material, thereby enhancing element recycling and ocean carbon productivity. Insights gained from the qualitative analysis of the extent of biogeochemical microbial activity and diversity across the temperature and chemical gradients that characterize these habitats, as reviewed herein, challenge traditional models of global ocean carbon productivity and provide the development of a new conceptual framework for understanding the quantitative metabolic potential and broad dispersal of the crustal microbial biome.